Tinea Amiantacea - Sarkar J; Sengupta B.N; Sharma M.K; Bhattacharya P; Barman M.K (Wolters Kluwer Medknow Publications, 1995)
Tinea amiantacea is a rare disease now-a-days. A case of this abnormality is reported.